Design and development of a web-based parenting portal - Ma, Zhongnan (Nanyang Technological University, 2020)
Having and raising a child is definitely one of life’s greatest joys and most important responsibilities. Throughout the parenting journey, many challenges come together with this little bundle of joy. Parents can easily find themselves confused and frustrated by the seemingly endless problems of parenthood. Therefore, this project aims to develop a web-based portal called Bundle of Joy that provides information and services related to babies and toddlers. Targeting at would-be parents and parents in Singapore, Bundle of Joy covers a wide range of topics from pregnancy to toddlers. Not only focusing on traditional parenting topics such as baby development, this portal also has a strong emphasis on modern-day challenges in Singapore (i.e., government financial schemes, cost of neighborhood kindergarten, etc.). Moreover, interactive user experience is one of the primary focuses of this project. Features that allow users to interact with will be heavily applied in the portal. By asking for user input and generating results based on it, more personalized user experiences could be achieved, further promoting user loyalty to this portal. In conclusion, ‘Bundle of Joy’ aims to be the one-stop portal to help parents in their child-raising journey in Singapore.